The Complete Sequence of the First Spodoptera frugiperda Betabaculovirus Genome: A Natural Multiple Recombinant Virus - Cuartas, Paola E. (2015)
Spodoptera frugiperda (Lepidoptera: Noctuidae) is a major pest in maize crops in Colombia, and affects several regions in America. A granulovirus isolated from S. frugiperda (SfGV VG008) has potential as an enhancer of insecticidal activity of previously described nucleopolyhedrovirus from the same insect species (SfMNPV). The SfGV VG008 genome was sequenced and analyzed showing circular double stranded DNA of 140,913 bp encoding 146 putative ORFs that include 37 Baculoviridae core genes, 88 shared with betabaculoviruses, two shared only with betabaculoviruses from Noctuide insects, two shared with alphabaculoviruses, three copies of own genes (paralogs) and the other 14 corresponding to unique genes without representation in the other baculovirus species. Particularly, the genome encodes for important virulence factors such as 4 chitinases and 2 enhancins. The sequence analysis revealed the existence of eight homologous regions (hrs) and also suggests processes of gene acquisition by horizontal transfer including the SfGV VG008 ORFs 046/047 (paralogs), 059, 089 and 099. The bioinformatics evidence indicates that the genome donors of mentioned genes could be alpha- and/or betabaculovirus species. The previous reported ability of SfGV VG008 to naturally co-infect the same host with other virus show a possible mechanism to capture genes and thus improve its fitness.